Prevalence of hepatitis C among HIV-1, HIV-2 and dually reactive patients: A multi-country cross-sectional survey in West Africa - Didier K. Ekouevi; Patrick A. Coffie; Boris K. Tchounga; Armel Poda; Antoine Jaquet; François Dabis; Serge P. Eholie (AOSIS, 2018)
Little is known on the impact of HIV-2 infection on HCV viral replication. The aim of the study was to compare HCV prevalence and viral replication based on HIV types in West Africa. A cross-sectional survey was conducted within the IeDEA HIV-2 West Africa cohort from March to December 2012. All HIVinfected adult patients who attended participating HIV clinics during the study period were included. Blood samples were collected and re-tested for HIV type discrimination, HCV serology and viral load. A total of 767 patients were enrolled: 186 HIV-1, 431 HIV-2 and 150 HIV-1&2 dually reactive. At time of sampling, 531 (69.2%) were on ART and median CD4+ cell count was 472/mm3. Thirty (3.9%, 95% CI 2.7-5.5) patients were anti-HCV positive (4.3% in HIV-1, 4.0% in HIV-1&2 dually reactive and 3.7% in HIV-2; p=0.91). Detectable HCV RNA was identified in 21 (70.0%) patients (100% in HIV-1 and HIV- 1&2 dually reactive vs. 43.8% in HIV-2; p=0.003). Systematic screening should be promoted and performed in this population, since HCV is now potentially curable in sub- Saharan Africa.